2018
DOI: 10.1159/000490572
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine Prevents Levosimendan-Induced Atrial Fibrillation

Abstract: Objectives: Levosimendan is a calcium sensitizer that is used as positive inotropic drug in acute decompensated heart failure. An increased incidence of atrial fibrillation after levosimendan-treatment was observed in clinical and experimental studies. Due to the limited range of antiarrhythmic drugs, the aim of the present study was to assess potential antiarrhythmic effects of ranolazine in levosimendan-pretreated isolated rabbit hearts. Methods: Twelve rabbit hearts were excised and retrogradely perfused em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Ranolazine is an FDA-approved antianginal agent with already known antiarrhythmic effects on the ventricular and atrial level in this [ 16 , 17 ] model, experimental models of other groups [ 9 ] and clinical trials [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ranolazine is an FDA-approved antianginal agent with already known antiarrhythmic effects on the ventricular and atrial level in this [ 16 , 17 ] model, experimental models of other groups [ 9 ] and clinical trials [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Late Na + current, through the actions of the sodium Ca 2+ exchanger, may impact intracellular Ca 2+ , contributing to further activation of CaMKII as well as driving the incidence of arrhythmogenic DADs. Ranolazine has been used successfully in rodents and large animals to block these changes and prevent the development of hypertrophy, HF, and arrhythmias (Rastogi et al, 2008;Figueredo et al, 2011;Glynn et al, 2015;Liang et al, 2016;Ellermann et al, 2018;Nie et al, 2019). However, results from clinical trials have been mixed with data supporting that ranolazine is safe with questionable efficacy in preventing AF recurrence (RAFAELLO trial), ventricular tachycardia (VT) or ventricular fibrillation (VF) following implantation of cardioverter defibrillator (RAID trial), or improving functional capacity in hypertrophic cardiomyopathy (RESTYLE-HCM trial) (De Ferrari et al, 2015;Bengel et al, 2017;Olivotto et al, 2018;Zareba et al, 2018).…”
Section: Therapeutic Targeting Of the Camkii Signaling Pathwaymentioning
confidence: 99%
“…Intracellular Ca 2+ homeostasis and subsequent contractility efficiency rely upon phosphorylation processes, which, in AF, are pathologically altered. Some recent studies have shown that levosimendan increases cerebral blood flow, decreases NT-proBNP (an indirect marker of adverse atrial remodeling), and improves atrial pump function on echocardiography; however, it also increases the occurrence of AF in these patients, an undesired effect attenuated by concomitant treatment with ranolazine, an inhibitor of the late inward sodium current [55]. Some very recent reports were focused on unravelling the pleiotropic, cardiovascular protective effects of sodium-glucose cotransporter-2 (SGLT2) inhibitors, a novel class of oral hypoglycemic medication that showed very promising results in the treatment of HF.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%